The Armadillo (Dasypus novemcinctus): A Witness but Not a Functional Example for the Emergence of the Butyrophilin 3/Vγ9Vδ2 System in Placental Mammals - Fichtner, Alina Suzann; Karunakaran, Mohindar Murugesh; Starick, Lisa; Truman, Richard W.; Herrmann, Thomas (Frontiers in Immunology, 2018)
Abstract (279 words) 1-5% of human blood T cells are Vγ9Vδ2 T cells whose TCR contain a TRGV9/TRGJP rearrangement and a TRDV2 comprising Vδ2-chain. They respond to phosphoantigens like isopentenyl pyrophosphate (IPP) or (E)-4-Hydroxy-3-methyl-but-2-enyl-pyrophosphate (HMBPP) in a butyrophilin 3 (BTN3)-dependent manner and may contribute to the control of mycobacterial infections. These cells were thought to be restricted to primates, but we demonstrated by analysis of genomic databases that TRGV9, TRDV2, and BTN3 genes coevolved and emerged together with placental mammals. Furthermore, we identified alpaca (Vicugna pacos) as species with typical Vγ9Vδ2 TCR rearrangements and currently aim to directly identify Vγ9Vδ2 T cells and BTN3. Other candidates to study this coevolution are the bottle-nosed dolphin (Tursiops truncatos) and the nine-banded armadillo (Dasypus novemcinctus) with genomic sequences encoding open reading frames for TRGV9, TRDV2 and the extracellular part of BTN3. Dolphins have been shown to express Vγ9- and Vδ2-like TCR chains and possess a predicted BTN3-like gene homologous to human BTN3A3. The other candidate, the armadillo, is of medical interest since it serves as a natural reservoir for Mycobacterium leprae. In this study, we analyzed the armadillo genome and found evidence for multiple non-functional BTN3 genes including genomic context which closely resembles the organization of the human, alpaca and dolphin BTN3A3 loci. However, no BTN3 transcript could be detected in armadillo cDNA. Additionally, attempts to identify a functional TRGV9/TRGJP rearrangement via PCR failed. In contrast, complete TRDV2 gene segments preferentially rearranged with a TRDJ4 homolog were cloned and co-expressed with a human Vγ9-chain. Phosphoantigen-reactivity of heterodimeric TCRs was not observed. So far, the lack of expression of TRGV9 rearrangements and BTN3 renders the armadillo an unlikely candidate species for phosphoantigen-reactive Vγ9Vδ2 T cells. This is in line with the postulated co-evolution of the three genes, where occurrence of Vγ9Vδ2 TCRs coincides with a functional BTN3 molecule.